Influence of degradable intake protein on site and extent of digestion in beef cows consuming low-quality, tallgrass-prairie forage - H.H. Köster; R.C. Cochran; E.S. Vanzant; G. St Jean; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1995)
Five Angus x Hereford cow s with ruminal and duodenal fistulas were used to evaluate the effect of providing increasing degradable intake protein (DIP) o n the site and extent of digestion of dormant, tallgrass-prairie forage. The DIP was provided from sodium caseinate, divided in two equal portions and infused intraruminally twice daily. Levels of DIP were: 0, 180, 360, 540, and 720 g/day. Supplemental DIP generally improved utilization of low quality forage, with maximum effects on duodenal N flow and forage organic matter intake at 540 g DIP/day.
Keywords: Cattlemen' s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Beef cows; Intake; Digestibility; Forage